2008
DOI: 10.1124/jpet.108.138784
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between Superoxide Accumulation and Nitroglycerin-Induced Tolerance

Abstract: We hypothesize that superoxide (O 2 . ) accumulation is not a crucial causative factor in inducing nitroglycerin (NTG) . accumulation may be an effect, rather than an initiating cause, of NTG tolerance.Nitroglycerin (NTG; glyceryl trinitrate) and other organic nitrates have been widely used to treat coronary artery disease in patients with stable and unstable angina, acute myocardial infarction, and congestive heart failure. When administered acutely, NTG relieves ischemic symptoms rapidly without serious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…production was observed in both NTG-tolerant- (Tsou et al, 2008) and GSSG-treated cells. In both cases, O 2 .…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…production was observed in both NTG-tolerant- (Tsou et al, 2008) and GSSG-treated cells. In both cases, O 2 .…”
Section: Discussionmentioning
confidence: 83%
“…A possible concern of the applicability of this work may arise because we used LLC-PK1 cells, a porcine kidney epithelial cell line, to examine the cellular mechanisms of nitrate tolerance. However, these cells have been used for studying the pathways of nitrate-induced activation and desensitization of cGMP response in several studies Schröder, 1998, 1999;Tsou et al, 2008) and have shown many parallel hallmarks of vascular nitrate tolerance, including the lack of tolerance and cross-tolerance toward strict NO donors such as SNAP, dose-dependent tolerance induction, and tolerance attenuation by vitamin C. We have attempted to examine cellular NTG tolerance in cultured human vascular smooth muscle cells. However, consistent with literature reports (Bennett et al, 1989), these cells, when cultured, were poorly responsive to NTG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations